Neuroendocrine Carcinoma of The Uterine Cervix: Clinicopathological Profile and Outcomes From a Tertiary Referral Center in Indonesia - Permatasari, Anita; Dewayani, Birgitta Maria; Yantisetiasti , Anglita (Jurnal Locus Penelitian dan Pengabdian, 2025)
Neuroendocrine carcinoma of the cervix (NECC) is a rare and aggressive cervical malignancy with poor prognosis. Data from Indonesia remain scarce. We retrospectively reviewed 55 cases of NECC diagnosed at Dr. Hasan Sadikin General Hospital, Bandung, between 2019 and 2025. Clinicopathological data included age, International Federation of Gynecology and Obstetrics (FIGO) stage, histologic subtype, lymphovascular invasion (LVI), and metastatic status. Overall survival (OS) was estimated using Kaplan–Meier analysis. Patients’ ages ranged from 24 to 82 years, with a median age of 46 years. Most cases were diagnosed at locally advanced stages (FIGO II–III, 54.5%), while 14 patients (25.5%) presented with distant metastatic disease (IVB). Small cell NECC was the predominant subtype, while large cell and admixed variants were less frequent. LVI was present in more than half of the cases. Distant metastases at diagnosis were identified in the lungs, bone, and liver. At the last follow-up, 25 patients (45.4%) had died. Kaplan–Meier analysis revealed a median OS of 14.5 months, with 1-year survival of 52% and 2-year survival of 42%. NECC in Indonesia presents mostly at locally advanced stages, with high rates of LVI and frequent metastases, leading to poor survival. These findings highlight the aggressive course of NECC and provide baseline data for future studies in Indonesia.